"Samuel Sami Everett and Rebekah Vince, eds., Jewish-Muslim Interactions: Performing Cultures Between North Africa and France, Liverpool, Liverpool University Press, 2020" - Miccoli, Dario (2021)
recensione del volume Samuel Sami Everett and Rebekah Vince, eds., Jewish-Muslim Interactions: Performing Cultures Between North Africa and France, Liverpool, Liverpool University Press, 2020